Two new species of Paratanytarsus (Diptera: Chironomidae) from southeast of Brazil - Trivinho-Strixino, Susana (Zootaxa, 2010)
The adults and immature stages of Paratanytarsus corbii sp. n. and the male adult of Paratanytarsus silentii sp. n. are described and illustrated. P. corbii larvae were collected on sediment and aquatic vegetation of the headwater of the Anhumas Reservoir (Américo Brasiliense, SP) and reared in laboratory to obtain the pupal exuviae and associated adults. The adult males of P. silentii were obtained from Malaise net put over the Córrego do Silêncio located in Parque Estadual do Jaraguá (São Paulo, SP). The shape of the anal point and the absence of anal point crests are the main characteristics that distinguish P. corbii and P. silentii males from the majority species of the genus. The arrangement of spines on tergites III–V separates the pupae of P. corbii from other species. The length of pedicels and the pecten epipharyngis design are diagnostic for the larvae of P. corbii.